Pengaruh Self Efficacy, Work Engagement dan Kompensasi Finansial terhadap Kinerja Karyawan PT. Sinergi Gula Nusantara (Jurnal Manajemen Kreatif dan Inovasi, 2026)
The influence of self-efficacy, work engagement, and financial compensation is crucial to determine the extent of their impact on employee performance at PT Sinergi Gula Nusantara PG Meritjan. By understanding these relationships, company management can assess how these factors affect employee performance and thereby formulate more targeted human resource planning and development strategies in the future. This study employed a saturated sampling technique, in which the sample consisted of all permanent employees of PT Sinergi Gula Nusantara PG Meritjan, totaling 77 respondents. Data were collected through questionnaires, observations, and interviews. The results of the analysis indicate that self-efficacy, work engagement, and financial compensation have a significant effect on employee performance, both partially and simultaneously. This is evidenced by the multiple linear regression analysis, which shows significance values below 0.05 and a coefficient of determination of 0.677 or 67.7%, indicating that self-efficacy, work engagement, and financial compensation explain 67.7% of the variance in employee performance.